Genomic analysis of an Ecuadorian individual carrying an SCN5A rare variant - Santiago Cadena-Ullauri; Patricia Guevara-Ramírez; Viviana A. Ruiz-Pozo; Rafael Tamayo-Trujillo; Elius Paz-Cruz; Daniel Simancas-Racines; Rita Ibarra-Castillo; José Luis Laso-Bayas; Ana Karina Zambrano (BMC Cardiovascular Disorders, 2024)
Abstract Background Ion channels, vital transmembrane protein complexes, regulate ion movement within cells. Germline variants in channel-encoding genes lead to channelopathies. The sodium channels in cardiac cells exhibit a structure of an alpha subunit and one to two beta subunits. The alpha subunit, encoded by the SCN5A gene, comprises four domains. Case presentation A fifteen-year-old Ecuadorian female with atrial flutter and abnormal sinus rhythm with no familial history of cardiovascular disease underwent NGS with the TruSight Cardio kit (Illumina). A likely pathogenic SCN5A gene variant (NM_188056.2:c.2677 C > Tp. Arg893Cys) was identified, associated with arrhythmias, long QT, atrial fibrillation, and Brugada syndrome. Ancestral analysis revealed a predominant European component (43.9%), followed by Native American (35.7%) and African (20.4%) components. Conclusions The participant presents atrial flutter and conduction disorders, despite lacking typical cardiovascular risk factors. The proband carries a SCN5A variant that has not been previously reported in Latin America and may be associated to her phenotype. The documented arginine-to-cysteine substitution at position 893 in the protein is crucial for various cellular functions. The subject’s mixed genetic composition highlights potential genetic contributors to atrial flutter, emphasizing the need for comprehensive genetic studies, particularly in mixed populations like Ecuadorians. This case underscores the importance of genetic analysis for personalized treatment and the significance of studying diverse genetic backgrounds in understanding cardiovascular diseases.